Species richness influences wine ecosystem function through a dominant species. (August 2016) - Boynton, Primrose J.; Greig, Duncan
Abstract: Increased species richness does not always cause increased ecosystem function. Instead, richness can influence individual species with positive or negative ecosystem effects. We investigated richness and function in fermenting wine, and found that richness indirectly affects ecosystem function by altering the ecological dominance of Saccharomyces cerevisiae . While S. cerevisiae generally dominates fermentations, it cannot dominate extremely species-rich communities, probably because antagonistic species prevent it from growing. It is also diluted from species-poor communities, allowing yeasts with lower functional impacts to dominate. We further investigated the impacts of S. cerevisiae and its competitors in high- and low-functioning wine communities, focusing on glucose consumption as an ecosystem function. S. cerevisiae is a keystone species because its presence converts low-functioning communities to communities with the same function as S. cerevisiae monocultures. Thus, even within the same ecosystem, species richness has both positive and negative effects on function.